2018
DOI: 10.1111/1462-2920.14093
|View full text |Cite
|
Sign up to set email alerts
|

Single cell observations show persister cells wake based on ribosome content

Abstract: Since persister cells survive antibiotic treatments through dormancy and resuscitate to reconstitute infections, it is imperative to determine the rate at which these cells revive. Using two sets of Escherichia coli persister cells, those arising after antibiotic treatment at low levels and those generated at high levels by ceasing transcription via rifampicin pretreatment (shown to be bona fide persisters through eight sets of experiments), we used microscopy of single cells to determine that the resuscitatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
155
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(173 citation statements)
references
References 52 publications
16
155
1
1
Order By: Relevance
“…The GFP reporter indicates transcription of rrsB (16S rRNA), gltT (tRNAglu), rrlB (23S rRNA) and rrfB (5S rRNA); hence, it indicates production of the three major rRNA building blocks. Although this is not a direct observation of 70S ribosomes, this method is a suitable proxy for the number of active ribosomes based on the measurement of rRNA concentrations and has been used frequently (Lu et al, 2009;Piques et al, 2009;Burger et al, 2010;Kim et al, 2018b), and we have verified its use by isolating ribosomes and comparing GFP fluorescence (Kim et al, 2018b). Hence, the increased persister cell resuscitation with RluD is directly due to the increase in active (70S) ribosomes of persister cells since persisters wake via ribosome activation (Kim et al, 2018b).…”
Section: Rlud Increases Active Ribosomes For Resuscitationmentioning
confidence: 85%
See 4 more Smart Citations
“…The GFP reporter indicates transcription of rrsB (16S rRNA), gltT (tRNAglu), rrlB (23S rRNA) and rrfB (5S rRNA); hence, it indicates production of the three major rRNA building blocks. Although this is not a direct observation of 70S ribosomes, this method is a suitable proxy for the number of active ribosomes based on the measurement of rRNA concentrations and has been used frequently (Lu et al, 2009;Piques et al, 2009;Burger et al, 2010;Kim et al, 2018b), and we have verified its use by isolating ribosomes and comparing GFP fluorescence (Kim et al, 2018b). Hence, the increased persister cell resuscitation with RluD is directly due to the increase in active (70S) ribosomes of persister cells since persisters wake via ribosome activation (Kim et al, 2018b).…”
Section: Rlud Increases Active Ribosomes For Resuscitationmentioning
confidence: 85%
“…Using a GFP reporter that indicates the number of 70S ribosomes in individual persister cells (Kim et al, 2018b), we found that overproducing RluD from pCA24N before making persister cells (i.e. before rifampicin treatment) makes 85% AE 6% of the cells have high ribosome fractions compared with 22% AE 2% of the cells that do not overproduce RluD (Fig.…”
Section: Rlud Increases Active Ribosomes For Resuscitationmentioning
confidence: 99%
See 3 more Smart Citations